Uncovering the life of your dreams : an enlightening story - Schneider, Bruce D. (Wiley, 2018)
Based on the true story of the authors transformational journey, this entertaining tale takes you on a journey of your own toward a more enlightened life filled with abundance, joy, and absolute freedom. --